Rebate in Islamic sale-based financing contracts: Bank Negara Malaysia guidelines on ibrāʾ versus conventional finance practice - Islam Kamal (ISRA International Journal of Islamic Finance, 2021)
Purpose - This paper aims to compare the rebate computation in Islamic sale-based financing contracts as proposed by Bank Negara Malaysia (BNM) in its guidelines on ibrāʾ (rebate) - with the rebate computation in conventional finance that is applicable to conventional loans, thus examining if there is a significant difference between the two approaches. Design/methodology/approach - The paper employs the qualitative analysis method, involving review and discussion of relevant literature. Subsequently, a quantitative analysis is utilized to compare both rebate computations: the one proposed by BNM for Islamic sale-based financing contracts and the conventional finance computation that is utilized in conventional loans. Findings - BNM's rebate computation for debts resulting from sale-based financing contracts does not differ from the conventional finance rebate computation applied to conventional loans; such similarity may raise the usury concerns that the conventional finance rebate computation raises. Research limitations/implications - The paper focuses only on the fixed profit rate rebate computation proposed by BNM guidelines. Practical implications - The results highlight the need for seeking another rebate computation to be applied in Islamic financial institutions in the case of mandatory bilateral rebate for sale-based financing contracts - a computation that differs from the practice utilized in conventional loans in order to avoid any usury implications associated with conventional finance computation. Originality/value - The paper examines the rebate practice proposed by BNM for sale-based financing contracts. Forcing a predetermined rebate computation in sale-based financing contracts could be plausible as BNM requires; however, the suggested computation might be questionable because it resembles conventional finance computation.
Keywords: 330; Bayʿ al murābahah; Daʾ wa taʾajjal; Ibrāʾ